Kwena Malapo: to belong to the city. - Grant, Taryn Ann (My University, 2014)
This thesis is based on a community called Kwena Malapo near Lanseria. It is a group of people that sit between the threat of relocation and the opportunity to develop along with the new proposed development of Cradle City. The land on which the informal settlement exists sits on the border of this development and the community are fighting to stay where they are. They lack basic services and infrastructure have poor education and no skills investment which makes them vulnerable. The aim of this thesis is to put forward the design of a community hub that will serve the community, give them an opportunity for learning and contribution as well as the ability to develop with the new economic growth, instead of facing relocation. Along with skills development and business opportunity the hub aims to serve the 13 informal settlements that surround Kwena Malapo.
Keywords: City planning--South Africa--Johannesburg.; Community development--South Africa.; Relocation (Housing)--South Africa.